Changes in the life history traits in Aedes aegypti selected for resistance to permethrin and thymol, a spatial repellent - Chelsea T. Smartt; Sara Farless; Natalie L. Kendziorski; Tse-Yu Chen; Yuexun Tian; Barry W. Alto; Sandy A. Allan; Cynthia C. Lord (PLoS ONE, 2025)
Mosquitoes are both pests and pathogen vectors. Exposure to insecticides for mosquito control may have unintended outcomes on mosquito biology, including evolution of insecticide resistance. Direct lethal effects from exposure to insecticides reduce population size but may also alter phenotypic traits among surviving adult mosquitoes (e.g., size, longevity, biting, susceptibility to pathogen infection), attributable to changes in density-dependence and sub-lethal exposure. Resistance has increased in many populations as a result of traditional contact insecticide mosquito control measures (e.g., pyrethroids). Spatial repellents, including essential oils, are an increasingly important area of mosquito control as spatial repellents deter entry into dwellings, decrease biting, and development of insensitivity to repellents has not been detected. Effects of exposure to these chemicals have not been well studied, however. This study investigates changes in life history and fitness costs in Aedes aegypti selected to be resistant to different doses of permethrin and thymol. Aedes aegypti selected to be resistant to a contact insecticide (permethrin) and spatial repellent (thymol) generally exhibited reduced adult longevity compared to the unselected (control) group but these differences depended on selection dose, meal type (unfed, blood-fed, sugar-fed) and mating status. Both avidity to blood feed and the number of eggs laid were higher in mosquitoes selected using both doses of thymol and a high dose of permethrin compared to control mosquitoes. Permethrin and thymol selection resulted in shortened and lengthened development times than controls, respectively. As with pyrethroid based chemicals, use of spatial repellents, such as thymol, may impact important life history traits in mosquitoes. Use of these chemicals may alter mosquito population dynamics and biting pressure. Our results support the notion that development of resistance to spatial repellents can have lasting effects on mosquito biology relevant to their ability to transmit pathogens. Testing of insensitivity to spatial repellents should be incorporated into control strategies, since repellency can be a strong selective force influencing reproduction (e.g., acquisition of a blood meal from a host).